SQL Injection: Analisis Efektivitas Uji Penetrasi dalam Aplikasi Web - Luthfi Arian Nugraha; Irwan Alnarus Kautsar; Arif Senjani Fitrani (LPPM UBHINUS MALANG, 2024)
In the continuously evolving digital era, information system security becomes crucial, particularly against SQL Injection attacks that threaten data integrity. This research aims to evaluate the vulnerability to SQL Injection in web applications and assess the effectiveness of penetration testing methods as a security measure. Utilizing a literature review and previous studies, this research identifies various attack techniques and defense strategies used to protect data. Through systematic penetration testing on ten websites, this study produces performance data reflecting the success rate of attacks and the time required for penetration. The results show variations in the effectiveness of penetration testing tools, with some sites exhibiting significant vulnerabilities. To enhance the security of web applications, this research suggests updating programming languages, implementing OOP and MVC paradigms, using Rest APIs, implementing WAFs, and utilizing CAPTCHAs. These findings provide insights for developing more robust and adaptive security strategies in the face of cyber threats.